Adaptive time step selection in the quasi-static methods of nuclear reactor dynamics. (July 2017) - Caron, D.; Dulla, S.; Ravetto, P.
Highlights: A method for the selection of the time steps in the quasi-static method is presented. Strategies for the adaptive selection of the shape and reactivity time steps are described. The method is applied to numerical test problems, studying the convergence behaviour. Abstract: Of the methods available by which to integrate the neutron and delayed neutron precursor balance equations in time, at present the quasi-static methods are among the most practical and favourable. However, the correct application of the quasi-static method requires the use of appropriately determined time steps, for both the reasons of accuracy and efficiency. This work presents a methodology for the adaptive selection of the time steps employed by the quasi-static method, thereby allowing the quasi-static approach to be applied in an efficient manner while maintaining a prescribed level of accuracy. The method is applied to and studied using some numeric test problems.